The influence of academic stress on the performance of basic education students at the Central University of Ecuador - Díaz-Parra, Jacqueline (2025)
Academic stress significantly affects the performance of university students, manifesting itself in various ways: physical, emotional, and cognitive. Previous studies indicate that 77% of people worldwide suffer from moderate or severe stress (United Nations Development Program, 2022). In Ecuador, research such as that by Moscoso and Barsallo (2018) reveals that 43.2% of students experience moderate academic stress. This research sought to evaluate the level of stress in students of in-person basic education. To do so, a non-experimental-descriptive methodology and a deductive method with a quantitative approach were used. The SISCO SV-21 Inventory was applied to 586 students, selected through stratified probability sampling by semester. The results showed that a severe level of stress prevails among students, ranging from 61% to 100%. The main stressors identified were homework overload (M=3.68) and the type of work required (M=3.58). The most frequent consequences included concentration problems (M=4.10) and feelings of depression (M=3.77). Coping strategies that stood out were emotional control (M=3.86) and focusing on positive aspects (M=3.62). Statistical analysis (χ2=150.530, p<.001) confirmed the relationship between the semester completed and the level of stress. These findings suggest the need to implement institutional programs to manage academic stress, especially aimed at first-semester students and those in advanced semesters.